Palmatina diminui a neuroinflamação em camundongos submetidos à isquemia cerebral focal permanente - Pereira, Juliana Fernandes (2017)
Stroke is chiefly characterized by a sudden neurological deficit formerly by ischemic and hemorrhagic processes in the central nervous system. Stroke is the second cause of death and the first cause of disability worldwide. Cerebral ischemia is a pathophysiologic condition triggered by blood supply decrease in the brain that leads to metabolic demand decrease required to its functioning. Palmatine is an alkaloid extracted from Chinese medicinal plants with known antioxidant and anti-inflammatory activity. The aim of this study was to evaluate the palmatine effect against neuronal death, memory deficits, inflammatory response and oxidative stress in mice subjected to focal cerebral ischemia induced by permanent middle cerebral artery occlusion (pMCAO). Ninety-sex Swiss male mice, weighting 30-35g, were divided into 6 groups: 1. sham-operated, 2. sham-operated treated with palmatine (20 mg/kg p.o.), 3. subjected to pMCAO and treated with vehicle, 4. subjected to pMCAO and treated with palmatine (0.2 mg/kg, p.o.), 5. subjected to PMCAO and treated with palmatine (2 mg/kg, p.o.) and 6. subjected to pMCAO and treated with palmatine (20 mg/kg, p.o.). Palmatine treatment was initiated 2 h after pMCAO induction and daily over a period of 4 days depending of the experimental design. Ischemic damage was assessed by TTC staining and neurological evaluation 24 h after pMCAO induction. Palmatine diminished ischemic area and enhanced neurological performance in mice subjected to pMCAO. Locomotor activity was assessed by open field test 72 h after PMCAO induction. Memory deficits were evaluated by Y maze test (working memory) and passive avoidance test (aversive memory). PMCAO induced memory deficits in mice and palmatine treatment reversed these deficits. Neuroinflammation was assessed through the measurement of GFAP/Iba-1/iNOS/COX-2/IL- 1β/TNF-α/NF-κB-imunohistochemistry with PMCAO significantly increasing neuroinflammatory and palmatine treatment reestablished it. Furthermore, oxidative stress was evaluated through the measurement of SOD-2-immunohistochemistry and synaptogenesis through the measurement of synaptofisin expression. However, no alteration was found between the groups. Our results suggest that palmatine has a remarkable neuroprotective effect probably by its neuroinflammatory activity, providing experimental evidence regarding the possible palmatine use as an adjuvant treatment to stroke.